Pengembangan Produk dan Perancangan Srategi Produt Life Cycle (PLC) untuk Meningkatkan Penjualan Gerabah dengan strategi Assesment Of Customer dan Analisis SWOT - Ayu, Baiq Dinda Puspita; Nasri, Muhammad Haris (Universitas Bumigora, 2024)
Pottery sales in East Masbagi have decreased after Covid 19 and in 2022, many art shops will still be affected by closing, so to know further, a good strategy is needed for pottery craftsmen in East Masbagi Village based on analysis to create various strategic options that can be chosen according to the problem. craftsmen, using SWOT analysis and assessment of customers to provide definite information for designing strategies using PLC. This research uses the Field Research type of research. The data in this research were obtained from the results of a Focus Group Discussion (FGD) with pottery craftsmen in East Masbagik. The results of the research show that based on the results of the customer assessment strategy and SWOT analysis which were processed using product life cycle (PLC) analysis, 4 decisive alternative strategies were obtained, which were then selected through the QSPM matrix. The results of the QSPM matrix show that the highest score is 2434, namely creating creativity by developing products to attract consumer interest in accordance with the reality that the existing products and designs produced are still eye-catching and there is not as much housing as possible.